THE CLUSTER INITIATIVE AS A SPECIAL ECONOMIC PROJECT: EUROPEAN AND UKRAINIAN PRACTICES - A. Yevstakhevych; I. Paryzkyi; N. Tomchuk-Ponomarenko; O. Yarova; B. Yatsykovskyy; A. Chukhlib (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The article examines the European and Ukrainian practices, on cluster initiatives as a special development of economic projects. It is noted that in connection with the development and spread of globalization processes in the world increases competitiveness in the market and enterprises need to introduce new ways to strengthen the competitiveness and development of their production capacities. It is determined that the cluster is a stable system of enterprises and institutions associated with the production of innovative products, using the achievements of self-developing research institutions, training and education of research organizations and commercial structures, stimulating entrepreneurial activity in science and commercialization of progressive technologies. Emphasis is placed on the fact that the trends of the new cluster economy cause the following processes: Globalization and localization of business, production, capital, as processes of movement to integrated actions, targeted involvement of the country’s potentials, industries, priority resources. Primary sphere of exchange, increasing influence of financial authorities, financial oligarchy, financial markets as an element of supercontrol, hyper-power, centers of influence on changes in the reproduction of national products. Rapid information progress and sustainable priorities of comprehensive intellectualization of labor in all spheres of human activity, capacity building of the knowledge system and its tools of influence on the new man, etc. It is noted that world practice shows that when a cluster is created, all the industries within it begin to support each other. Competitive suppliers contribute to the development of consumer industries in the country. They provide them with technology, stimulate the development of common factors of production, and generate new producers. A single industry, competitive on the world market, can create a number of new interconnections, providing access to skilled labor, taking advantage of family diversification, or encouraging the emergence of new divorces. Overview that the development of cluster economy will contribute to the development of territorial communities and infrastructure of the regions, stimulate demand for education, now going through hard times, stop the outflow of human capital with subsequent employment in Ukraine, as well as stimulate innovation among young people, help improve their competitiveness in the global economic and political arena.